Apt to change: The problematic of language awareness and language aptitude in age-related research - Singleton, David (Studies in Second Language Learning and Teaching, 2014)
Language awareness and language aptitude often crop up in discussion of various second language acquisition phenomena, including age-related phenomena. There is a troublesome and ongoing definitional and theoretical problem in this connection: Different researchers have different perspectives on what is to be included in the respective notions; on how do to measure language awareness, on the one hand, and language aptitude, on the other; and on how or whether to differentiate the two constructs in terms of innateness versus experience. This article begins by addressing the entire problematic of the conceptualization of language awareness and language aptitude. The language awareness/aptitude issue features in the maturational debate in connection with two claims. First, it is discussed in relation to the view that second-language (L2) learning of older individuals is explicit (whereas that of younger individuals is implicit). Second, it is referred to in regard to the notion that there are older L2 learners who appear to be able to “beat” the critical period thanks to high levels of language aptitude. The article critically explores both these propositions and concludes that neither is particularly safe, especially given the uncertain state of the relevant research context.